Effect of Different Inducer Sources on Cellulase Enzyme Production by White-Rot Basidiomycetes Pleurotus ostreatus and Phanerochaete chrysosporium under Submerged Fermentation - Osmond Datsomor; Qi Yan; Louis Opoku-Mensah; Guoqi Zhao; Lin Miao (Fermentation, 2022)
Cellulase enzymes attract a lot of research due to their industrial application. Diverse cellulase-producing organisms and substances that induce cellulase are highly sought after. This study aimed to evaluate the effect of different inducer sources on cellulase production by white rot fungi P. ostreatus CGMCC 3.7292 and P. chrysosporium CGMCC 3.7212 under submerged fermentation employing a completely randomized experimental design. The different inducer sources tested were nitrogen (yeast, potassium nitrate, sodium nitrate, ammonium sulphate, aqueous ammonia and urea), carbon (malt extract, glucose, fructose, carboxymethylcellulose, starch and xylose) and agro-biomass (stevia straw, wheat straw, oat straw, alfalfa straw, corn cobs and corn stover). These inducer sources strongly impacted enzyme activities by P. ostreatus CGMCC 3.7292 and P. chrysosporium CGMCC 3.7212. The suitable nitrogen and carbon inducer sources for cellulase activity by P. ostreatus and P. chrysosporium were yeast (1.354 U/mL and 1.154 U/mL) and carboxymethylcellulose (0.976 U/mL and 0.776 U/mL) while the suitable agro-biomass were wheat straw (6.880 U/mL) and corn stover (6.525 U/mL), respectively. The least inducer sources in terms of nitrogen, carbon and agro-biomass for cellulase activity by P. ostreatus and P. chrysosporium were urea (0.213 U/mL and 0.081 U/mL), glucose (0.042 U/mL and 0.035), xylose (0.042 U/mL and 0.035 U/mL) and stevia straw (1.555 U/mL and 0.960 U/mL). In submerged fermentation, the cellulase enzyme activity of P. ostreatus in response to various inducer sources was relatively higher than P. chrysosporium.